Answers

2016-04-28T10:41:26+05:30
Let the number be x. And it's additive inverse will be -x. Now dividing it by 12 that is -x/12. Now one less than three times it reciprocal is 3/x -1. As they both are equal X/12 = 1 - 3/x. X/12 = x -3/x. X^2 = 12x - 36. X^2 - 12x + 36 = 0. Therefore ( x -6 )^2 = 0. And hence x - 6 = 0. And x = 0
0
how can be x = 0
And hence x - 6 = 0. And x = 0 .........is this correct?
No that x = o has come by mistake...x = 6 only
then edit ur answer
The Brainliest Answer!
2016-04-28T12:50:30+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Let the required number = x
according to the question,
additive inverse of the  number = -x
condition : -x/12 = 3/x -1
                 -x/12 = (3-x)/ x
                 - x²    = 36 - 12x
                   x² - 12x +36 = 0
                   x ² -6x- 6x + 36 =0
                   x(x - 6) - 6( x - 6) = 0
                   (x-6)(x-6) = 0
                   x = 6
                   therefore , the number is 6.
                
1 5 1